PROSPECTS OF DEVELOPMENT OF ACADEMIC WRITING AND EFFECTIVE BILINGUAL COMMUNICATION AT SFU (the international scientific-practical conference "Academic writing and effective bilingual scientific communication, SFU, November, 2013) (Proceedings of Southern Federal University. Philology, 2014)
Djumailo O.A.Keywords: bilingualism, academic writing, training, structuring, rhetoric.In this article the author describes in detail the schedule of the international scientific-practical conference, which was held in SFU in November, 2013. The attention to the problems of academic writing on the part of the management of the University is due to the strategic goal which was put before SFU–to be among the leaders of science and education of Russia. Trainings of the conference on the principles of structuring, grammar skills, rhetoric, public speaking in an academic environment, caused great interest of participants among students and teachers of linguistic and non-linguistic SFU faculties and other universities of the city.